OPTIMIZING PRICING STRATEGIES: THE ROLE OF FULL COSTING IN ACCURATE PRODUCTION COST ANALYSIS - Widhajati, Eni; Rakhmawati, Henny; Nika Audina, Yulisa (Universitas Tulungagung, 2024)
This study explores the implementation of full costing as a method to enhance the accuracy of production cost calculations and its implications for pricing strategies in small and medium enterprises (SMEs). Using a case study of Kerupuk Rambak Pak Djarwo, the research compares traditional costing practices with the full costing method. Data were collected through interviews, observations, and documentation, focusing on production cost data from 2023. The findings reveal a significant difference in production costs between the two methods, with full costing providing a more comprehensive accounting of overhead costs such as managerial salaries and utilities. This approach ensures more accurate pricing, aligning with true production costs, which is critical for competitiveness and profitability. However, the study identifies challenges in adopting full costing, including resource constraints and a lack of expertise. The research emphasizes the need for capacity-building initiatives and technological integration to facilitate the transition. The findings offer actionable insights for SMEs and policymakers to enhance financial management practices and foster long-term sustainability in competitive markets.